Development of Student Activity Sheets (SAS) Using Mind Mapping Strategy to Enhance Creative Thinking Skills in the Topic of Buffer Solutions - Fernanda Febrya Ayu Putri; Mitarlis (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to develop a Student Activity Sheet (SAS) using mind mapping strategies that can be applied as a learning tool to enhance students’ creative thinking skills in the topic of buffer solutions. This study employs a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate), with a focus on the Develop stage. A limited pilot test was conducted at State Senior High School 22 Surabaya involving 36 11th-grade students using a One-Group Pre-Test Post-Test design. Feasibility was evaluated based on validity, practicality, and effectiveness. The SAS was deemed valid by three validators with a mode of ≥ 4 on all aspects of content and construct validity. In terms of practicality, the average lesson implementation reached 97.83%, student activity 98.82%, and student response 96.67%, all categorized as highly practical. Regarding effectiveness, the pre-test and post-test for mind mapping showed an average N-gain score of 0.76 (high category), while creative thinking skills showed an average N-gain score of 0.72 (high category). These results indicate that SAS with the mind mapping strategy is suitable for use as a learning tool to enhance students’ creative thinking skills regarding buffer solutions.